The Effect of Entrepreneurship Education and Government Support on Start-Up Growth in Bogor - Ruby Galuh Septino (North Press, 2024)
This study investigates the effect of entrepreneurship education and government support on the growth of start-up businesses in Bogor, Indonesia. Using a quantitative research design, data was collected from 50 start-up entrepreneurs through a structured questionnaire and analyzed using SPSS version 25. The results reveal that both entrepreneurship education and government support have a positive and significant impact on start-up growth. Entrepreneurship education, in particular, plays a more prominent role in fostering business growth by equipping entrepreneurs with the necessary skills and knowledge to manage and expand their ventures. Government support, while significant, offers external resources that complement the internal capabilities developed through education. These findings highlight the importance of an integrated approach, where educational programs and government policies work together to support start-up development. The study concludes with recommendations for enhancing entrepreneurship education and optimizing government support to promote start-up growth in emerging markets.